Integração e transmissão de preços no mercado internacional de algodão - Caixeta, Ana Caroline Dias (2016)
The aim of this study was to analyze the integration of prices in the Brazilian and international market cotton considering transaction costs . For this purpose we analyzed the CEPEA and NYBOT indices, representing the national and international market cotton, respectively, from January 2000 to December 2014. With the methodology Model Correction Vector Error with Threshold (TVEC) with two regimes. The first regime corresponded to the cotton price changes in the short term, which represented 5,6% of the sample. In the second scheme, which corresponded to 60,1 % of the sample are the deviations that are influenced by short- and long -term changes . The results showed a significant presence of transaction costs in both schemes, which negatively affects the price transmission process, hindering the integration of prices in the cotton market.